Effectiveness of the National Health Insurance (JKN) Mobile Application in Improving Health BPJS Services at Puskesmas Medan Tuntungan - Panjaitan, Nuraisyah Wulandari; Siregar, Annisa Rizki Ramadani; Purba, Anita Zahra Putri; Gurning, Fitriani Pramita (PROMOTOR, 2024)
The influence of digitalization and the rapid development of technology is widely used in all aspects of life in society including in the field of health services. The health center as one of the health service units that spearheads public health services often faces challenges in providing effective and efficient services. The research method used in this research is descriptive qualitative. Based on data from the Medan Tuntungan Health Center, until June 2024 the number of BPJS health membership was 24,309 people. Furthermore, the number of people who registered JKN Mobile Application accounts in May 2024 was 14 people. The effectiveness of JKN mobile at the Tuntungan Health Center based on the results of research with health workers and the community who are also JKN Mobile user patients is still less than optimal in providing training to the field by BPJS officers who are responsible for this.